Pengaruh Religiusitas Dan Literasi Keuangan Syariah Terhadap Minat Menabung Di Bank Syariah (Studi Kasus Pada Mahasiswa FEB Universitas Dharma Andalas) - Farendiva Ananta Ramadhan; Ingra Sovita (CV. ITTC INDONESIA, 2026)
This study aims to analyze the influence of Religiosity and Islamic Financial Literacy on the Interest in Saving at Islamic Banks, focusing on students at the Faculty of Economics and Business (FEB), Dharma Andalas University. The research is motivated by the significant growth of the Islamic financial industry in Indonesia, contrasted by the persisting preference for conventional banking among students. The research utilizes a quantitative approach with multiple linear regression analysis. Hypothesis testing was conducted using partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R^2). The results show that, partially, the Religiosity variable has a positive and significant effect on saving interest (t_count 9.839 > t_table 1.968; sig 0.000). The Islamic Financial Literacy variable also has a positive and significant effect (t_count 5.144 > t_table 1.968; sig 0.000). Simultaneously, both variables significantly influence saving interest with an F_count of 171.012. The Adjusted R Square value of 0.545 indicates that Religiosity and Islamic Financial Literacy contribute 54.5% to the variation in students' interest in saving at Islamic banks, while the remaining 45.5% is explained by other factors outside this study.